Canine Skull Digitization and Three-Dimensional Printing as an Educational Tool for Anatomical Study - Silveira, Erick Eduardo da; Lisboa Neto, Antonio Francisco da Silva; Sabino Pereira, Helton Carlos; Ferreira, Janaina Santos; Santos, Amilton Cesar dos; Siviero, Fabio; Fonseca, Ricardo da [UNESP]; Assis Neto, Antonio Chaves de (Univ Toronto Press Inc, 2021)
This article aims to standardize 3D scanning and printing of dog skulls for educational use and evaluate the effectiveness of these anatomical printed models for a veterinary anatomy course. Skulls were selected for scanning and creating 3D-printed models through Fused Deposition Modeling using acrylonitrile-butadiene-styrene. After a lecture on skull anatomy, the 3D-printed and real skull models were introduced during the practical bone class to 140 students. A bone anatomy practical test was conducted after a month; it consisted in identifying previously marked anatomical structures of the skull bones. The students were divided into two groups for the exam; the first group of students took the test on the real skulls, whereas the second group students took the test on 3D printed skulls. The students' performance was evaluated using similar practical examination questions. At the end of the course, these students were asked to answer a brief questionnaire about their individual experiences. The results showed that the anatomical structures of the 3D printed skulls were similar to the real skulls. There was no significant difference between the test scores of the students that did their test using the real skulls and those using 3D prints. In conclusion, it was possible to construct a dynamic and printed digital 3D collection for studies of the comparative anatomy of canine skull species from real skulls, suggesting that 3D digitalized and printed skulls can be used as tools in veterinary anatomy teaching.
Keywords: 3D printing, 3D scanner, veterinary technology, teaching veterinary anatomy